Unconventional split aptamers cleaved at functionally essential sites preserve biorecognition capability - Wang, Ruoyu (2021)
Split aptamers (SPAs) are a pair of oligonucleotide fragments generated by cleaving a long parent aptamer. SPAs have many compelling advantages over the parent aptamer such as sandwich target binding, optimized concise structure, and low cost. However, only a limited number of SPAs have been developed so far because the traditional theory restricts the splitting to the functionally dispensable site that many parent aptamers do not possess. In this work, the traditional mechanism and hypothesis that SPAs can also be generated by splitting the parent aptamer at the functionally essential site while still preserving the biorecognition capability are challenged. To prove the hypothesis, three SPAs with Broken initial small-molecule binding Pockets (BPSPAs) are discovered and their binding capabilities are validated both in the wet lab and in silico. An allosteric binding mechanism of BPSPAs, in which a new binding pocket is formed upon the target binding, is revealed by all-atom microsecond-scale molecular dynamics simulations. Our work highlights the important role of MD simulations in predicting the ligand binding potency with functional nucleic acids at the molecular level. The findings will greatly promote discovery of new SPAs and their applications in molecular sensing in many fields.